The role of innovative approach on employees’ job performance: a study of government sector in Abu Dhabi, UAE - Abdulla Lari, Mohamed Ahmed Darwish (2020)
Transformation of the public sector driven by global competition towards improving services and facilities has been the focus of the UAE government in the recent decade. Hence, this study uncovered the effect of innovations on employees’ job performance in the government sector. The study adopted quantitative approach where data was collected through questionnaires survey and analysed statistically. Questionnaire was designed based on the literature review where the main content of the questionnaire are factors on innovations and employees’ job performance in the government sector. The survey utilized simple random sampling methods among employees in the Ministry of Culture, Youth and Community Development UAE. The respondents were staffs from management, human resource, employee relations, operations and training departments. A total of 300 questionnaires were distributed randomly and 265 were returned. Collected data have undergone data screening and found 258 responses were valid for further analysis. At the initial stage, the collected data were analysed using descriptive and univariate approach in SPSS software. It was found that five most significant factors affecting the oil and gas company performance are rewards and recognition, low employee turnover, effective behaviour, assuring job security and effective support system. The collected data was used to developed and assessed PLS-SEM model of casual relationship between the factors affecting oil and gas company performance using SmartPLS software. The model has two components which are measurement component and structural component. Measurement component is the relationship between the factor/variable/item and the independent/latent construct. It was been assessed with three criteria which are indicator reliability, convergent validity and discriminant validity. The results indicate that each of assessment criteria has achieved with the stipulated guidelines for PLS model assessment. While structural model is the relationship of independent construct with the dependent construct. The model was assessed based on five criteria which included path coefficients (β), coefficient of determination (R2 value), effect size (f2), and predictive relevance (q2). Results of the assessment found that the model has substantial explaining power in representing the impact of the five groups of factors affecting the oil & gas company performance. In term of path analysis, Leadership and Job satisfaction groups of factors have significant relationship with the company performance. In term of effect size and predictive relevance, the model showed that only two group of factors which are Leadership and Job satisfaction were having small effect or relevant to company’s performance while other groups have no effect size. Even though some of the results are not as expected as the hypotheses but it can be concluded that the structural model has been validated statistically. The data was to develop mediation model in SEM-AMOS software which comprises of innovation dimensions as independent constructs, job performance as dependent construct and mediates by technology construct. The model was assessed at two levels where at the measurement level was to ensure that the variables are in the respective construct using confirmatory factor analysis and at structural level to determine path relationship between the constructs. The overall results indicate that the innovation dimensions have positive effect on employees’ job performance. Unfortunately, the technology has no mediation effects to the relationship between innovation dimensions and employees’ job performance. It is hoped that this study will be a viable tool for improving job performance in the UAE government sector.